Military requisitions in French law - Konarski, Marcin Jerzy (The Opole Studies in Administration and Law, 2022)
The subject of this analysis is related to the French legal regulations in the field of military requisitions as an element of a coherent system of State defence, which is based in the normative sphere on the fundamental legal act – the Code of Defence (Le code de la defense) of 2004. In the course of his discussion, the author presents the scope of legal solutions relating to military requisitions, the procedure of their performance, the system of compensation and indemnities as well as criminal sanctions established for the violation of requisition regulations.